Search Engine Optimization in the field of organization and representation of information and information retrieval - Camossi, Gustavo [UNESP]; Teixeira, Heytor Diniz [UNESP]; Rodas, Cecilio Merlotti (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2024)
Introduction: The amount of information available on the Web is expressive, which makes its retrieval difficult, implying the use of mechanisms that assist in the search process. In this context, search engines have become fundamental, being the target of studies, especially in Information Science, since the theories and techniques in the dimension of the Organization and Representation of Knowledge and Information Retrieval arebased on the construction of a domain and its representation. In this perspective, this study aims to verify how Search Engine Optimization techniques from marketing can be employed together to improve the organization and representation of information in search engines, enabling greater accuracy in the search results obtained by users. Method: The methodology adopted has a descriptive exploratory character, defined as bibliographic research to discuss the theme and present the discussions, based on Information Science. Results: The results indicate that SEO techniques can contribute and innovate in the way of making information available to society, providing organization, retrieval, access and use of information in various environments. Conclusions: We conclude that Search Engine Optimization techniques can provide support in the construction of digital informational environments, treating and organizing information, contributing effectively to Information.
Keywords: Search Engine Optimization; Information retrieval; Digital information environments; Knowledge organization and representation